Adsorption of formulated chlorpyrifos on selected agricultural soils of Terengganu - Tay, Joo Hui; Marinah, Mohd Ariffin; Norhayati, Mohd Tahir (Malaysian Analytical Sciences Society, 2010)
In this study, the adsorption of commercially formulated chlorpyrifos (trade name Kensban®, 20% a.i.) in three soil samples (0-25cm depths) collected from vegetable farms in the state of Terengganu, Malaysia has been investigated using a batch technique. Analysis of the insecticide was carried out using gas chromatography equipped with nitrogen and phosphorus detector. Result indicated that, soils contained higher organic matter and clay content exhibited a much stronger adsorption affinity for the insecticide. In addition, soil pH was also observed to play a role in influencing the adsorption affinity of this insecticide where a higher adsorption was observed for soils with lower pH values. Results from this study clearly showed that, in agreement with previously reported studies, soil properties particularly organic matter content, clay content and pH play an important role in controlling the sorption behaviour of chlorpyrifos insecticide. However, it must be conceded that the measured adsorption in this study might also be influenced by a number of processes occurred in the soil, such as complex interaction between chlorpyrifos, solvent, emulsifier, water and the soil sorption sites since the applied chlorpyrifos was a commercial formulation.